UJI EKSPREMENTAL KARAKTERISTIK BRIKET ARANG BERBAHAN BAKU LIMBAH SEKAM PADI SIAM DAN PANDAK - A'yan Sabitah; Apip Amrullah; Akhmad Syarief (INFO-TEKNIK, 2019)
Utilization of waste rice husk, especially in South Kalimantan, is not very efficient. Therefore, it needs more maximal utilization, for example it is used to manufacture alternative fuels in the form of charcoal briquettes. The effort to maximizing utilize waste rice husk as charcoal briquettes, we need to know the combustion characteristics. The study, we used a variation of the ratio between siam rice husk charcoal in the peat region areas and pandak is located in the tidal areas with adhesives of 5%, 10% and 15% respectively. Characteristics of testing follows SNI 01-6235-2000. Based on the results of the study, it is known that the charcoal waste of rice husk waste with a percentage of 5% adhesive has a good value compared to the addition of other adhesives, where siam rice husk has a water content of 4.9% and pandak has a higher moisture content of 5.0%, whereas for husk heating values Pandak rice is larger with a value of 5063.6 cal / gram, compared to siam rice husk with a value of 4894.5 cal / gram.